Interferometric backward third harmonic generation microscopy for axial imaging with accuracy beyond the diffraction limit. - Daaf Sandkuijl; Lukas Kontenis; Nuno M Coelho; Christopher McCulloch; Virginijus Barzda (PLoS ONE)
A new nonlinear microscopy technique based on interference of backward-reflected third harmonic generation (I-THG) from multiple interfaces is presented. The technique is used to measure height variations or changes of a layer thickness with an accuracy of up to 5 nm. Height variations of a patterned glass surface and thickness variations of fibroblasts are visualized with the interferometric epi-THG microscope with an accuracy at least two orders of magnitude better than diffraction limit. The microscopy technique can be broadly applied for measuring distance variations between membranes or multilayer structures inside biological tissue and for surface height variation imaging.